2017
DOI: 10.3892/mmr.2017.7366
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture serum inhibits TNF-α-mediated chondrocyte inflammation via the Ras-Raf-MEK1/2-ERK1/2 signaling pathway

Abstract: The Ras-Raf-mitogen-activated protein kinase kinase (MEK)1/2-extracellular signal-regulated kinase (ERK)1/2 signaling pathway contributes to the release of chondral matrix-degrading enzymes and accelerates the degradation of articular cartilage. Electroacupuncture (EA) treatment has been widely used for the treatment of osteoarthritis (OA); however, the mechanism underlying the effects of EA on OA remains unclear. Therefore, the present study evaluated the anti-inflammatory effects and potential underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Research has shown that acupuncture can reduce TNF- α and IL-6 levels in serum [ 31 , 32 ], as well as inhibit the degree of intracellular inflammatory response [ 33 – 35 ]. The results of our study showed that the levels of IL-6 and TNF- α were significantly, markedly higher in the model group compared with the normal group, indicating that stress ulceration increases the infiltration of proinflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that acupuncture can reduce TNF- α and IL-6 levels in serum [ 31 , 32 ], as well as inhibit the degree of intracellular inflammatory response [ 33 – 35 ]. The results of our study showed that the levels of IL-6 and TNF- α were significantly, markedly higher in the model group compared with the normal group, indicating that stress ulceration increases the infiltration of proinflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of I-BET151 was applied in the recent report about the effect of I-BET151 on rheumatoid arthritis synovial fibroblasts, and in the same report, the authors found that delayed treatment with I-BET151 showed lower effect than that pretreatment with I-BET151 [ 14 ]. The dose of IL-1β and TNF-α was mentioned in the previous studies of chondrocytes [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Neuromodulation with acupuncture is used to control pain and inflammation in humans [116], and likely has a similar physiologic response in horses. In rodent models, it has been shown that acupuncture may protect against articular cartilage erosion [118] as well as chondrocyte inflammation [119], and these effects may help in clinical cases of cervical OA. It is the authors' opinion that many horses experiencing neck pain respond well to acupuncture of the cervical region and acupuncture may help prolong treatment intervals when used in conjunction with other therapies.…”
Section: Acupuncturementioning
confidence: 99%